City of eternal spring - Weaver, Afaa Michael (Pitt poetry series., 2014)
This is the final book in the Plum Flower Trilogy by Afaa Michael Weaver, published by the University of Pittsburgh Press. The two earlier books, The Plum Flower Dance: Poems 1985 to 2005 and The Government of Nature, reveal similar themes that address the author's personal experience with childhood abuse through the context of Daoist renderings of nature as a metaphor for the human body, with an eye to recovery and forgiveness in a very eclectic spiritual life. City of Eternal Spring chronicles Weaver's travels abroad in Taiwan and China, as well as showing the limits of cultural influence.